A qualitative investigation of a mindfulness‐based yoga program for educators: How program attendance relates to outcomes. Issue 7 (9th April 2020) - Schussler, Deborah L.; Harris, Alexis R.; Greenberg, Mark T.
Abstract: Contemplative professional development interventions seek to help educators manage stress and improve emotion regulation, yet the mechanisms of action revealing how they result in positive psychological and physical outcomes remain unclear. Using focus groups based on levels of attendance, this qualitative study examined how educators with different levels of attendance perceived their experiences in Community Approach to Learning Mindfully (CALM), a mindfulness‐based yoga program. Using theory‐driven and data‐driven codes, two researchers adopted a thematic analytical approach to independently code interviews. Results suggest that individuals across all groups indicated participation in CALM stimulated awareness of some kind—somatic, emotional, or awareness of thought patterns. However, participants who attended more frequently were more likely to practice mindfulness informally during routine activities. This increased skill integration was associated with improved outcomes. Program acceptability was high across attendance groups although those with low attendance felt stressed making time to attend the program. Collegiality emerged as an important benefit and catalyst for reinforcing practices. Implications for professional development are discussed, including the role of collegiality and the importance of program readiness. Practitioner Points: Educators who attended Community Approach to Learning Mindfully (CALM) sessions consistently two or more times per week expressed increased emotion and somatic awareness which were related to improved outcomes related to their resilience and well‐being. Educators with the least consistent and frequent attendance had different expectations for what they would receive from CALM suggesting that individual's program readiness may impact how they experience a yoga‐based mindfulness program. Collegiality was a positive outcome of CALM and a catalyst for reinforcing skill integration.